Efeito da terapia com Laser de Baixa Potência (LBP) em modelo experimental de Doença Pulmonar Obstrutiva Crônica (DPOC): participação da via purinérgica - Moraes, Gabriel de Assis Cunha (2016)
Currently, chronic obstructive pulmonary disease (COPD) has an impact on morbidity and mortality throughout the world with high prevalence and a high economic and social cost. It is characterized by slow and progressive airflow limitation, triggered by the inhalation of harmful particles present in cigarette smoke. In this context, several experimental models have been proposed, aiming at the discovery of new therapeutic options. In this regard, low-power laser therapy (LBP) is a relatively new and effective therapy for very low cost, no side effects and possible use in the treatment of chronic pulmonary diseases. In the present study we study some parameters in animals with COPD undergoing therapy diode laser (660 nm), 30 mW, 60 s per point (3 points per application) for 15 days prior to euthanasia. The protocol used for COPD induction consisted of nebulized female C57BL / 6 with cigarette smoke for 75 days (2 times / day). On the day 76, the animals were anesthetized, tracheotomy, canulated and bronchoalveolar lavage (BAL) was collected. Structural and functional parameters were studied, the total and differential counts of cells recovered from BAL fluid, cytokine levels (IL-1 , IL-6, IL-10, IL-17, TNF- and CXCL1/KC) as well as the accumulation of mucus and collagen. It also performed lung histology to quantify the number of lymphocytes in the airway, and bronchial remodeling. Moreover, we will evaluate the expression of the purinergic receptors P2Y2 and P2X7 in the homogenate of lung tissue by Western Blotting technique. The results showed that LLLT significantly reduced the number of total cells in the bronchoalveolar (BAL), the levels of cytokines IL-6, IL-1β, IL-17, TNF-α and CXCL1/KC, mucus production and collagen, cell death, alveolar enlargement, as well as the expression purinergic P2X7 and increased cytokine anti-inflammatory (IL–10). Therefore,we suggested that the laser 808nm is effective to reduce lung inflammation in an experimental model of chronic obstructive pulmonary disease (COPD).